2023
DOI: 10.1038/s41431-023-01456-z
|View full text |Cite
|
Sign up to set email alerts
|

The molecular genetics of nELAVL in brain development and disease

Meghan R. Mulligan,
Louise S. Bicknell

Abstract: Embryonic development requires tight control of gene expression levels, activity, and localisation. This control is coordinated by multiple levels of regulation on DNA, RNA and protein. RNA-binding proteins (RBPs) are recognised as key regulators of post-transcriptional gene regulation, where their binding controls splicing, polyadenylation, nuclear export, mRNA stability, translation rate and decay. In brain development, the ELAVL family of RNA binding proteins undertake essential functions across spatiotempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…This could indicate that the spermatogonia of mice are primarily type A intermediate spermatogonia, while those of pigs are predominantly type B spermatogonia [68]. In pig spermatogonia, the expression of ELAVL2, a little-studied ELAVL family member [69], is particularly active. Interestingly, the significantly differentially expressed genes identified in the pseudotime analysis of pig spermatogonia indicated that ELAVL2 was highly expressed in pig spermatogonia.…”
Section: Discussionmentioning
confidence: 99%
“…This could indicate that the spermatogonia of mice are primarily type A intermediate spermatogonia, while those of pigs are predominantly type B spermatogonia [68]. In pig spermatogonia, the expression of ELAVL2, a little-studied ELAVL family member [69], is particularly active. Interestingly, the significantly differentially expressed genes identified in the pseudotime analysis of pig spermatogonia indicated that ELAVL2 was highly expressed in pig spermatogonia.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of circRNAs in the brain is a molecular landmark across animals 1,12,13 . Considering the similarity, in terms of sequence and expression patterns, of neuronal ELAV-like (nELAV) proteins from flies to humans 29,57,58 , conserved mechanisms may be at play to regulate intron pairing and neuronal circRNA biogenesis. Moreover, the predominantly cytoplasmically localized human nELAV protein HuD binds to a quarter of all brain-expressed circRNAs as well as many host transcripts 59 ; in context with our findings, this raises the hypothesis that in evolutionarily distant species, nuclear nELAV proteins (such as ELAV) mediate circRNA biogenesis, and that binding of mature circRNAs by cytoplasmic nELAVs (such as HuD) regulates their local expression and function.…”
Section: Discussionmentioning
confidence: 99%
“…These were implicated in HPC LTP of the slow inhibitory postsynaptic currents -an inhibitionrelated LTP that Nova2 knockout mice lack, suggesting specific long-term changes of synaptic plasticity (Huang et al, 2005). Interestingly, NOVA and RBFOX might work as splicing regulators in a synergistic manner by binding the same mRNA, skipping exons when bound upstream or on target, or including the exon when bound downstream (Raj & Blencowe, 2015;Zhang et al, 2010); see also Figures 8C, Figure and stress response (Clayton et al, 1998;Keene, 1999;Mulligan & Bicknell, 2023). ELAVL2 has not been widely studied in rodents due to high mortality rate at weaning following growth…”
Section: Novamentioning
confidence: 95%
“…impairments, but has been implicated in memory formation in other vertebrate models (Mulligan & Bicknell, 2023). ELAVL3 upregulation during development promotes cell fate of progenitors of GABAergic inhibitory neurons (see Figure 1.10C), and loss in murine neural stem cells delays neuronal differentiation (Grassi et al, 2018).…”
Section: Novamentioning
confidence: 99%
See 1 more Smart Citation